Materials with Memory - Graffi, Dario; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
R. Bouc, G. Geymonat: Periodic problems in thermoviscoelasticity.- A. Day: The thermodynamics of materials with memory.- M. Fabrizio: Sulla nozione di stato nella termomeccanica dei continui.- G. Fichera: Analytic problems of hereditary phenomena.- M. Ribaric: The black box approach and systems with memory.- R.S. Rivlin: The theory of constitutive equations.-
R. Bouc, G. Geymonat: Periodic problems in thermoviscoelasticity -- A. Day: The thermodynamics of materials with memory -- M. Fabrizio: Sulla nozione di stato nella termomeccanica dei continui -- G. Fichera: Analytic problems of hereditary phenomena -- M. Ribaric: The black box approach and systems with memory -- R.S. Rivlin: The theory of constitutive equations.-.
Keywords: Mathematics; Differential equations, partial; Thermodynamics; Mathematics; Partial Differential Equations; Thermodynamics